Analysis of ACCC failure of composite core glass transition temperature reduction due to brittle damage. (December 2022) - Qi, Di; Yin, Tao; Xiao, Hongyi; Luo, Zhixian; Deng, Tao; Jiang, Yu
Graphical abstract: Highlights: The ACCC core is more brittle than the ACSR core and is more prone to brittle damage. The load distribution of the ACCC conductor may change due to the brittle damage of composite core. The glass transition temperature of the composite core is a key to the operating temperature of the ACCC conductor. Abstract: The failure analysis of the Aluminum Conductor Steel Reinforced (ACSR) was often based on conventional failure methods such as strength and fracture, and the failure analysis of the Aluminum Conductor Composite Core (ACCC) usually followed the analysis methods of the ACSR. This research proposed a new ACCC failure mode based on the glass transition temperature ( T g ) of composite materials. In this paper, a fracture accident of a 500 kV overhead transmission line was discussed. Firstly, impact test found that composite core of the ACCC was more brittle than steel core of the ACSR, and the brittle damage of the composite core was inferred as the cause of the accident in combination with fracture analysis. Then, thermal-structural coupling analysis showed that the axial stress of aluminum wires increased to 33 MPa after the brittle damage of the composite core. Subsequently, thermoelectric coupling analysis showed that the operating temperature ( T ) of conductor was raised to 151 °C after the increment of the axial stress of the aluminum wires. Finally, in dynamic mechanical analysis, it was shown that the T g of faulty composite core was reduced to 146.3 °C. According to investigation, the T of conductor was greater than the T g of epoxy resin in the faulty composite core, resulting in a decrease in the tensile strength of the composite core, which eventually led to the ACCC failure. The failure mechanism proposed in this paper can provide a reference for the prevention and maintenance of ACCC lines in power grid system.